PEMBAHARUAN PEMIKIRAN ISLAM DI TIMUR TENGAH: KONTRIBUSI HASSAN AL-BANNA DAN PENGARUHNYA TERHADAP KEMERDEKAAN NEGARA-NEGARA MUSLIM - Mahfud Alizar; Syamsul ‘Aimah (Al-Wihdah: Jurnal Pendidikan Islam, 2024)
Islamic thought reform in the Middle East has played a significant role in shaping the political, social, and religious dynamics of the region, particularly in the context of the struggle for independence from Western colonialism. One of the central figures in this reform movement is Hassan al-Banna, the founder of the Muslim Brotherhood (Ikhwanul Muslimin) in Egypt. This article discusses al-Banna's contributions to renewing Islamic thought by emphasizing the integration of Islam and politics, the implementation of Sharia, and resistance to imperialism. The research combines case study and content analysis methods, with data collected through in-depth interviews, observations, and written documents, which are then analyzed thematically. Hassan al-Banna, the founder of the Muslim Brotherhood, formulated the ideology and primary goals of this movement to establish Islam as a comprehensive system of life, encompassing all aspects of personal and social life. Al-Banna stressed the importance of implementing Sharia law in governance to create a just and moral society. The Muslim Brotherhood aims to restore the glory of Islam through social, political, and economic reforms based on Islamic teachings, with a focus on education, da'wah (Islamic preaching), and empowering the Muslim community. Additionally, the movement seeks to combat colonialism and Western influence, which is perceived as corrupting Islamic values. Al-Banna's thoughts and activities inspired resistance movements against colonialism and spurred the revival of Islam in various Muslim countries, playing a crucial role in the struggle for independence and the establishment of states based on Islamic principles.